TEACHING AND SOLVING INSTALLMENT SALES PROBLEMS. - Zimering, Max (The Accounting Review, 1952)
In teaching the topic of installment sales to students, or in explaining procedures to bookkeepers of enterprises selling for cash as well as by the installment plan, one encounters difficulty in the adjustments brought about by repossessions. The student as well as the bookkeeper is confused as to the percentage to use in the adjustment, the profit or cost percentage. After determination of the percentage, difficulty is encountered in its application. Both the student and the bookkeeper are further troubled by the fact that after clearing the deferred profit account for the percentage of profit contained in the unpaid installment accounts and crediting the repossession loss account which appears on the books, a profit may result on the repossession which should be refunded to the purchaser. The writer has used for many years a method which requires no adjusting entries for repossessions and eliminates the possibility of suits by purchasers to recover the profit, if any, resulting from repossessions under Section 21 of the Uniform Conditional Sales Act.